17p-5=14-9(5p+9)

Simple and best practice solution for 17p-5=14-9(5p+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17p-5=14-9(5p+9) equation:



17p-5=14-9(5p+9)
We move all terms to the left:
17p-5-(14-9(5p+9))=0
We calculate terms in parentheses: -(14-9(5p+9)), so:
14-9(5p+9)
determiningTheFunctionDomain -9(5p+9)+14
We multiply parentheses
-45p-81+14
We add all the numbers together, and all the variables
-45p-67
Back to the equation:
-(-45p-67)
We get rid of parentheses
17p+45p+67-5=0
We add all the numbers together, and all the variables
62p+62=0
We move all terms containing p to the left, all other terms to the right
62p=-62
p=-62/62
p=-1

See similar equations:

| 2(i+2)=10 | | -4(12+p)=-20 | | 5x-6+7=15/3x | | 4(7x+4)=16 | | -4(-2n+2)=12n | | 4(7x+4)=6 | | 5h-4=6 | | 5x+5x+5x+5x=40 | | 7=3-2d | | x+.2x=3.133 | | -2(5+7s)=3(-6s+2) | | y=-3(1+1) | | -n16=2/ | | -n16=2 | | -20g-3(-g-16)=-11g+18-8g | | -4q=-6q−10 | | 3x+22=x-4 | | -c+8=7c | | 3(6x-2)=-18 | | 9b+10=-b | | -20t=-5(3t-5) | | 1/2(4x+2)=67 | | -20t=-15+25 | | -8=16=n | | 5x+6-3x-2=8 | | -3=-5k-43 | | 68=n | | 3z/10-5=2 | | 2/3+n=39 | | 10=9h+1 | | 5n+2n-6=2n-4n-2 | | 5.1b=-19.95+3b |

Equations solver categories